Studi Kesinambungan Fiskal Pada Variabel Makro Ekonomi Indonesia: Analisis VAR - Wardhono, Adhitya; Gema Qori’ah, Ciplis; Ayu Wulandari, Christina Dwi (Jurnal Ekonomi Kuantitatif Terapan, 2015)
This research was identify determine the fiscal structure formation and the impact of foreign debt on fiscal sustainabilityin Indonesia. The model is described by a variable fiscal sustainability of foreign debt and fiscal macro variables as independent variables. Empirically, this model using time series data in the form of quarterly data began in 2004.I - 2012.IV, the focus of this study using two methods of analysis: descriptive narrative qualitative analysis and causal analysis using VAR (Vector Auto Regressive). The results of this study demonstrated through two tests of hypotheses, which test the IR (Impulse Response) and VD (Variance Decomposition). IR estimation results indicate that there are  reciprocal relationship among SBI, foreign debt and oil price. The VD test indicate that SBI, inflation and oil price are more dominant in influencing fiscal sustainability in Indonesia.
Keywords: fiscal sustainability; foreign debt; VAR